Pre-service physical education teachers’ attitudes toward inclusive physical education: Subject specificity and measurement invariance - Braksiek, Michael (German journal of exercise and sport research, 2022)
A teacher’s positive attitude is an important factor for successful inclusive physical education (PE). PE teachers’ attitudes are shaped during PE teacher education (PETE) programs. Thus, a valid instrument is needed not only for assessing pre-service PE teachers’ attitudes toward inclusive PE but also for evaluating the effect of PETE programs in general and the effect of specific parts of such programs (e.g., seminars) on the development of those attitudes. Regarding the measurement of this attitude, little is known about how a subject-specific attitude toward inclusive education is related to general attitudes toward inclusive education. In this study 362 pre-service PE teachers’ attitudes toward inclusive education in general and inclusive PE were assessed using two general attitude scales and one PE-specific attitude scale. By conducting confirmatory factor analyses (CFAs), the factorial and convergent validity of the PE-specific scale was investigated. Results showed that the scale measures attitude toward inclusive PE adequately and that this attitude is related to general attitudes toward inclusive education. In addition, the measurement invariance of the scale among different degree programs of the pre-service PE teachers as well as group differences in the assessed attitude depending on the degree programs were investigated using multigroup CFA. The results support the use of the scale in the context of PETE for inclusion, but also point to general difficulties regarding attitude measurement in the context inclusive of (physical) education.